Paediatric burn wound patients: blood transfusion and requirements in the peri-operative period - Grobbelaar, Adriaan Ockert (Division of Plastic and Reconstructive Surgery, 2023)
The concept suggesting primary excision and immediate grafting as the definitive treatment for a thermal burn is not new (1 ). To avoid the sequelae of local and systemic sepsis, early excision of burn eschar to remove all devitalized tissue has been a widely accepted method of treatment of deep burns since 1929, when Wells performed total excision and grafting of electric burns (2). While the technique has many advantages, it is not without significant complications. Haemorrhage accompanying burn wound excision can be deceptively large, as can the metabolic stress associated with large surgical procedures performed in the post-burn period (3).